Evaluation of p-nitrobenzoic acid using Lowenstein–Jensen medium and rapid immunochromatographic test for early differentiation between Mycobacterium tuberculosis complex and non-tuberculous mycobacteria - Obulesu Gundala; Praveen Kumar V; Ramanesh Murthy; Salma Mahaboob R (Asian Journal of Medical Sciences, 2022)
Background: Mycobacterium tuberculosis (MTB), Mycobacterium bovis, Mycobacterium africanum, Mycobacterium canetti, and Mycobacterium microti are all members of the MTB complex [MTBC], which cause tuberculosis. Mycobacteria other than TB also known as non-tuberculous mycobacteria [NTM]. Aims and Objectives: The purpose of this study was to see how accurate and efficient the MPT64 Ag fast test and Lowenstein–Jensen (LJ) medium with p-Nitrobenzoic acid (PNB) was in differentiating MTB and NTM. Materials and Methods: This Prospective cross-sectional, diagnostic study was conducted in the department of Microbiology, Chalamadaanandarao Medical college, Karimnagar, Telangana. India. The study was conducted from September 2020 to September 2021. The study was preapproved by the Institutional ethical and research committee. Results: PNB inhibits the growth of MTBC, whereas NTM species were resistant. MPT64 is a protein antigen secreted specifically by the members of MTBC. This study was carried out to establish the accuracy and efficiency of LJ medium with PNB and MPT64 immunochromatography test (ICT) in differentiation between MTB and NTM. Of the 426 culture positive isolates tested, 382 (89.67%) were recovered from pulmonary specimens and 44 (10.32) from extrapulmonary sources. Of the 426 isolates tested for the presence of MPT64 antigen, 407 (95.53%) were found positive for ICT test. Whereas, 18 (4.22%) isolate and were considered as NTM and 408 as MTBC (95.77%) by selective inhibition by PNB in LJ medium. Conclusion: According to our findings, the SDbioline kit is a fast, accurate, and reliable approach for separating MTB from NTM for TB management. MPT64ICT results were compared to culture smear results, which was particularly informative in the situation of MPT64ICT negative isolates with liquid cultures.